Prevalence and predictors of hypertension in cardiac recipients - A. O. Shevchenko; E. A. Nikitina; N. P. Mozheiko; I. Yu. Tyunyaeva; N. N. Koloskova (Вестник трансплантологии и искусственных органов, 2017)
Aim. The study was aimed to assess the prevalence and risk factors of hypertension in cardiac recipients.Materials and methods. End-stage heart failure patients who received cardiac transplant between 01.01.2013 and 31.12.2016 in V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs (Moscow) and survived 3 months after surgery were included and followed up for 999.4 ± 774.3 (108–1587) days. Young patients (<18 y/o) and patients after repeated (n = 18) or multi-organ transplantation (n = 3) were excluded.Results. 353 cardiac recipients aged 45.6 ± 1.6 years (18.1% females and 81.9% males) were enrolled into the study. Hypertension was prevalent in 17.6, 42.8, 62.3 and 71.4%, respectively, before, in 3 months, in 1 year, and 3+ years after the transplantation. The study revealed significant relationship between post-transplant hypertension incidence and pre-op body mass index (р = 0.026), serum creatinine (р < 0.001), preexisting hypertension (RR = 1.36, р = 0.022) and renal failure, as well as donor heart posterior wall thickness (р = 0.034), post-transplant dialysis (RR = 1.85, р < 0.001), and antibody mediated rejection episodes (RR = 1.7, р = 0.001). Uncontrolled hypertension in cardiac recipients was related to poor compliance and new-onset post-transplant renal failure.Conclusion. Hypertension is highly prevalent among our population of cardiac recipients. The combination of various etiologic mechanisms, multiplex therapy and subjective factors calls for the careful individual patient management.